EFEKTIVITAS KINERJA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) PROVINSI RIAU TAHUN 2013 DALAM MENANGANI KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) - Seriahni Haloho; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Family is supposed to be a refuge for the whole family. However, in many households in the range of activity it became a place of suffering and torture as an act of violence. Integrated Service Center for Women and Children (P2TP2A) Riau Province as agencies that deal with cases of domestic violence (domestic violence) in general, the effectiveness of its performance is not maximized. The presence of constraints such as human resources are not adequate, facilities and infrastructure that have not been supportive, cooperation with relevant agencies that still needs to be improved. The problem in this study is how the effectiveness of Riau P2TP2A performance in achieving its goal of handling domestic violence and the factors to influence the effectiveness of the organization's performance.This study aims to determine the effectiveness of the performance P2TP2A Riau Province in 2013 in dealing with cases of domestic violence and to determine the factors that influence the effectiveness of the performance P2TP2A Riau Province in 2013 in dealing with cases of domestic violence.This study used qualitative research methods to the study of descriptive data. In collecting the data, the researcher used interview techniques, observation and documentation specified by purposive random sampling technique.From the analysis of the qualitative descriptive data that Riau P2TP2A Performance Effectiveness in handling domestic violence cases categorized yet effective. Therefore, the advice given in the last part of the study is how to improve the effectiveness of the performance of the Integrated Center for Women and Children (P2TP2A) Riau Province.Keywords: effectiveness, performance, domestic violence